Outline and focus of female gymnasts' individualized training process for balance beam exercises at advanced specialization stage - Gorelov, A. A.; Artemova, E. N.; Rumba, O. G. (Theory and Practice of Physical Culture, 2017)
This paper is aimed to consider the issue of individualized workout sessions of female gymnasts exercising on the balance beam. The authors have analyzed the anthropometric data, neurodynamic properties, functional state parameters, physical working capacity indicators, level of technical skills of the highly qualified female gymnasts and have come to the conclusion that the latter ones have to be divided into certain typological groups. Each group is different in the preferential development of certain motor conditions, neurodynamic properties, type of vegetative regulation, levels of trait and state anxiety, and anthropometric features. Moreover, the authors have not identified any strong connections between the studied parameters. It is the evidence of individuality of the subjects and proves the absence of typological group specifics. The results confirm that individualized workout sessions on the balance beam are highly important and should be based on differentiated approach to every female gymnast.